1975
DOI: 10.1016/0042-6822(75)90058-6
|View full text |Cite
|
Sign up to set email alerts
|

Localization of adenovirus DNA replication in KB cells

Abstract: The localization of adenovirus type 5 DNA replication has been investigated by both fractionation of isolated nuclei and electron-microscope autoradiography. Biol. 40,[65][66][67][68][69][70][71][72][73][74][75][76] reveals that pulse-labeled adenovirus type 5 DNA cosediments with the nuclear membrane. On the basis of this finding it can be supposed that the site of viral DNA replication is at the nuclear membrane. However, electron-microscope autoradiography of infected cells shows that the pulse-labeled vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

1976
1976
1995
1995

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 34 publications
3
8
0
Order By: Relevance
“…The IF structures appeared randomly throughout the nucleoplasm, with no apparent association with the nuclear membrane. If DBP does function in viral DNA replication, this result is in accord with the reports that group C adenovirus DNA replication occurs throughout the nucleus and not in association with the nuclear membrane (36,41).…”
Section: Resultssupporting
confidence: 89%
“…The IF structures appeared randomly throughout the nucleoplasm, with no apparent association with the nuclear membrane. If DBP does function in viral DNA replication, this result is in accord with the reports that group C adenovirus DNA replication occurs throughout the nucleus and not in association with the nuclear membrane (36,41).…”
Section: Resultssupporting
confidence: 89%
“…As shown in Figure IA the distribution of Ad2 DNA within a HeLa cell nucleus is in multiple discrete foci or 'replication factories' which are not nucleoli (9)(10)(11)15,16). Figure 1A is a computer reconstructed composite of all optical sections and represents the total Ad2 DNA in a single HeLa cell nucleus.…”
Section: Intranuclear Localization Of Ad2 Dna In Hela Cellsmentioning
confidence: 99%
“…Our data on 3-D localization of Ad2 replication factories are consistent with both previous EM and M banding studies for intranuclear compartmentalization of adenovirus DNA replication and suggest a way that the apparently contradictory data can be reconciled. The EM data indicated that tritiated adenovirus DNA could be found in sections throughout the nucleus (9)(10)(11). We have seen that Ad2 replication factories were associated with the nuclear envelope, but often they were large and extended into the nuclear interior.…”
Section: Intranuclear Localization Of Ad2 Dna In Hela Cellsmentioning
confidence: 99%
See 2 more Smart Citations